Analysis of the Impact of Overtime on Work Productivity and Occupational Safety and Health in the Lembean–Marawas Road Project in North Minahasa Regency - Jeny Lembang; Arthur H. Thambas; Grace Yoyce Malingkas (Journal of World Science, 2026)
This study aimed to analyze the effects of work motivation (X1), occupational health (X2), and occupational safety (X3) on worker productivity (Y) during overtime implementation in the Lembean–Marawas Road Preservation Project, North Minahasa Regency, and to evaluate the effectiveness of overtime work on workers’ physical productivity. The study employed a quantitative approach, with data collected through questionnaires distributed to 24 respondents and analyzed using IBM SPSS Statistics and Jamovi for validation and comparative testing. The F-test results indicated that work motivation, occupational health, and occupational safety simultaneously had a significant effect on worker productivity (F-count = 6.224; Sig. = 0.004), explaining 48.3% of the variance in productivity (R² = 0.483). Among the independent variables, work motivation had the strongest influence, with the highest regression coefficient (0.482). The physical productivity analysis showed that overtime was effective for stone masonry work (E = 1.0675) but ineffective for BJTP-280 plain reinforcement steel work (E = 0.4155), indicating that overtime effectiveness varied depending on the type of construction activity. The results obtained from SPSS and Jamovi produced consistent values, confirming the reliability of the statistical analysis.